ANATOMICAL STUDY FOR SUBGENERA PRUNUS L. AND CERASUS PERS. (ROSACEAE) LEAVES IN KURDISTAN REGION-IRAQ - Hasan, Ameena M.; Shahbaz, Saleem E.; Abdulrahman, Shamiran S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Mature leaves fully expanded, undamaged were used in this study for leaf anatomy (blade, midrib and petiole) for 12 taxa of subgenera Prunus and Cerasus (P. cerasifera Ehrh., P. domestica subsp. domestica L., P. domestica subsp. syriaca (Borkh.) Janchen ex Mansfeld, P. domestica subsp. insititia (L.) C. K. Schneid, P. domestica subsp. italica (Borkh.) Gams ex Hegi, P. armeniaca var. armeniaca, P. armeniaca cv. Saeede Meraime, P. microcarpa var. pubescens (Bornm.) Meikle, P. microcarpa var. microcarpa, P. brachypetala (Boiss.) Walp., P. mahaleb L. and P. cerasus L.). Also trichome length and frequency on areole part of leaf blade for each taxon were measured. All taxa were characterized by bifacial mesophylls which consist of palisade parenchyma in the upper side and spongy layer in the lower side. The investigated taxa divided according to the number of palisade parenchyma layers in three groups. The shape of midrib, petiole transverse section and shape of the vascular bundles were important diagnostic values used for identifications of taxa. The leaves of all investigated taxa of subgenera Prunus and Cerasus have unicellular trichomes with different shapes kinds present on leaves blade of all studied taxa. Mostly the trichomes in abaxial side areole longer than the trichomes in the adaxial side, also the frequency of trichoms in the abaxial face was significantly higher than in the adaxial face.